(untitled) (Barqaror Taraqqiyot va Rivojlanish Tamoyillari, 2024)
This article explores interactive methods of teaching econometrics to economics students. Econometrics, the application of statistical and mathematical techniques to economic data, can be a challenging subject to grasp. However, by incorporating interactive teaching methods, educators can enhance student engagement, critical thinking, and practical application of econometric concepts. This article discusses various interactive approaches, such as case studies, group projects, simulations, classroom experiments, and online tools. It also highlights the importance of peer instruction, industry partnerships, and practical applications in fostering student learning. The benefits of these interactive methods include improved understanding of econometric techniques, hands-on experience with real-world data analysis, and the development of essential skills for empirical economic analysis.